Evaluation of modified paediatric logistic organ dysfunction scoring system in predicting the outcome in critically ill children - George, John P.; Namboodiripad, Aparna (International Journal of Contemporary Pediatrics, 2018)
Background: The Pediatric Logistic Organ Dysfunction (PELOD) score has been earlier validated for scoring of children in the Pediatric Intensive Care Unit (PICU). We have modified the PELOD score to adapt to resource limited settings by replacing Partial pressure of Oxygen (PaO2) / Fraction of inspired oxygen (FiO2)ratio, Partial pressure of carbon dioxide (PaCO2), and mechanical ventilation by three new variables i.e. Respiratory rate, Chest retraction and Peripheral Capillary Oxygen Saturation (SpO2). Aim of this study was to assess the 'Modified PELOD' scoring system and correlate it with the prognosis of children in the PICU. Methods: A prospective, observational, hospital-based study on 75 critically ill patients admitted in the PICU from age one month to 15 years was done, during a period of one year, from June 2015 to May 2016. The modified PELOD scoring system was calculated for the patients during the first 24 hours of admission. Patients were followed up until they got discharged from the PICU or died. Results: Modified PELOD scores ranged from 1- 42 in this study, of which patients with higher values had worst prognosis. Modified PELOD score ≥23 had increased risk of mortality. Conclusions: The Modified PELOD score can be used to predict outcome even in resource limited settings. The mortality rate increases with increase in number of organs having dysfunction. Length of stay less than 48 hours is critical in terms of monitoring and management, as the chances of mortality are high during this period.